Case Markers in Purbiya Raji in Comparative Perspective - Dhakal, Dubi Nanda (Nepalese Linguistics, 2023)
This paper presents the case markers in Purbiya Raji (PR) comparing them with its other varieties. As expected, the variations in case marking is attested across Raji varieties. The variations of the case marking is also seen among the speakers of the same variety in Naukule Raji. While the elder speakers do not use the dative-accusative case marker, younger people use it. The ergative case marker -i can be reconstructed to Raji-Raute languages.